The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1365-2656.13667
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of gut microbiota data in the ‘eye of the beholder’: A commentary and re‐evaluation of data from ‘Impacts of radiation exposure on the bacterial and fungal microbiome of small mammals in the Chernobyl Exclusion Zone’

Abstract: Evidence that exposure to environmental pollutants can alter the gut microbiota composition of wildlife includes studies of rodents exposed to radionuclides. Antwis et al. (2021) used amplicon sequencing to characterise the gut microbiota of four species of rodent (Myodes glareolus, Apodemus agrarius, A. flavicollis and A. sylvaticus) inhabiting the Chernobyl Exclusion Zone (CEZ) to examine possible changes in gut bacteria (microbiota) and gut fungi (mycobiota) associated with exposure to radionuclides and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 79 publications
(158 reference statements)
2
19
0
Order By: Relevance
“…In summary, we agree with Watts et al (2022) that faecal samples may be indispensable for longitudinal studies, or where destructive sampling is otherwise not logistically or ethically possible.…”
Section: Faece S Ver Sus G Ut Sampling In Microb Iome S Tudie Ssupporting
confidence: 83%
See 4 more Smart Citations
“…In summary, we agree with Watts et al (2022) that faecal samples may be indispensable for longitudinal studies, or where destructive sampling is otherwise not logistically or ethically possible.…”
Section: Faece S Ver Sus G Ut Sampling In Microb Iome S Tudie Ssupporting
confidence: 83%
“…To demonstrate their point, Watts et al (2022) identified candidate resident and non‐resident taxa using Microfungi Collections Consortium (http://www.microfungi.org/table1) and FUNGUILD v.1.2 (Nguyen et al, 2016). They then filtered possible non‐resident fungi from the fungal dataset published by Antwis et al (2021).…”
Section: Implications Of Fungal Taxa Filteringmentioning
confidence: 99%
See 3 more Smart Citations